GAMBARAN PERILAKU MASTURBSASI/ONANI PADA MAHASISWA DI PERGURAN TINGGI KOTA MEDAN - Arifin Arifin; Putra Apriadi Siregar (CV. Adiba Aisha Amira, 2023)
Masturbation behavior is deviant behavior due to dependence on viewing pornographic sites in adolescents, masturbation behavior does not look at age and among both young and old, both men and women. While masturbation is the gratification of sexual desire which is done only for a moment, this research was made to help change the behavior of a teenager who is addicted to masturbation/masturbation. The method used in this journal is quantitative research using a descriptive survey approach which aims to describe the description of masturbation/masturbation behavior in college students in Medan. As for the sample in this study as many as 30 people. The sampling technique uses the Accidental Sampling technique. Data processing was carried out using the SPSS 26.0 application with univariate analysis. This univariate analysis aims to describe the distribution and frequency of the research variables. The conclusion of this study is to show an overview of masturbation behavior among students at tertiary institutions in the city of Medan with a total of 30 respondents by taking samples using an accidental sampling technique in which the sample is collected, namely any patient who meets the researcher by chance and is suitable as a data source. The number of respondents was 30 students with 14 male respondents (46.7%) and 16 female respondents (53.3%), with an average age of respondents namely. 19 years old amounted to 10 people (33.3%), 20 years old 13 people (43.3%), 21 years old 5 people (16.7%) and 22 years old 2 people (6.7%). As for the number of descriptions of masturbation behavior in students for the total category b, it is higher with a frequency of 17 people (56.7%). This shows that there are not too many differences even though they dominate the high category. For category c, the number of frequencies that exist for the description of masturbation/masturbation in college students in the city of Medan dominates the bad category with a total of 18 people (60%). This shows that the description of the bad category is more dominant than the good category. The results of this research can be used as input for related parties to change the pattern of habits that are carried out, and it is hoped that both the campus itself will provide a deeper understanding to change these deviant habits.